2014
DOI: 10.1371/journal.pone.0103043
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Morphine Exposure In Vitro Alters Proliferation and Differentiation of Neural Progenitor Cells and Promotes Apoptosis via Mu Receptors

Abstract: BackgroundChronic morphine treatment inhibits neural progenitor cell (NPC) progression and negatively effects hippocampal neurogenesis. However, the effect of acute opioid treatment on cell development and its influence on NPC differentiation and proliferation in vitro is unknown. We aim to investigate the effect of a single, short term exposure of morphine on the proliferation, differentiation and apoptosis of NPCs and the mechanism involved.MethodsCell cultures from 14-day mouse embryos were exposed to diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 56 publications
0
43
1
Order By: Relevance
“…Alternatively, it may be that opioids act through a different pathway which does not produce the neuropathologic findings we examined, or that current techniques are not well suited to detect the effects of opioids on the brain. Basic science studies suggest that opioid exposure may reduce the number of neuronal cells, decrease neuronal progenitor cell proliferation, and increase apoptosis,[6, 7] which could conceivably lead to cognitive impairment without an increase in neurofibrillary tangles or neuritic plaques. If opioid exposure decreases cognitive reserve, it may enhance the impact of existing neuropathologic changes, ultimately leading to dementia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, it may be that opioids act through a different pathway which does not produce the neuropathologic findings we examined, or that current techniques are not well suited to detect the effects of opioids on the brain. Basic science studies suggest that opioid exposure may reduce the number of neuronal cells, decrease neuronal progenitor cell proliferation, and increase apoptosis,[6, 7] which could conceivably lead to cognitive impairment without an increase in neurofibrillary tangles or neuritic plaques. If opioid exposure decreases cognitive reserve, it may enhance the impact of existing neuropathologic changes, ultimately leading to dementia.…”
Section: Discussionmentioning
confidence: 99%
“…[5] On the other hand, morphine decreased neuronal cell density and increased apoptosis in a hippocampal cell culture model,[6] and in mouse fetal brain cells, short-term morphine exposure reduced cell proliferation and increased apoptosis. [6, 7] Morphine also promotes hyperphosphorylation of tau, a key component of neurofibrillary tangles. [8] Taken together, these findings suggest a need to investigate the potential association between prescription opioid use and neuropathologic changes.…”
Section: Introductionmentioning
confidence: 99%
“…It plays a crucial role in controlling the perception of intense pain and serving as a connecting link in the central analgesic regulatory system [35]. And it is recently reported that the MOR mechanism is involved in the increased apoptosis of neural progenitor cells and enhanced differentiation of neuronal and glial cells induced by acute administration of morphine [36]. And some studies propose that MOR proteins are in fact not downregulated but instead desensitized and uncoupled from downstream signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the apoptotic effects of morphine are not limited to neurons. Morphine-induced cell death has also been reported for neuroprogenitor cells, 51 T cells, 52 microglia, 53 macrophages, 54 and astrocytes. 49,55 As noted above, some studies suggest that morphine induces cell death by increasing FasL expression and activating downstream targets of the Fas receptor, including Caspases-3 and 8.…”
mentioning
confidence: 84%